Factors affecting cervical cancer screening among Yemeni immigrant women in Klang Valley, Malaysia: A cross sectional study - Al-Oseely, Sarah; Abdul Manaf, Rosliza; Ismail, Suriani (Public Library of Science, 2023)
Introduction Cervical cancer is a significant public health problem for women worldwide. It is the fourth most frequent cancer in women globally. While early detection of cancerous lesions through screening tests leads to a better prognosis and a better chance of being cured, the number of people who go for screening is still low, especially for groups that are marginalized, like immigrant women.